2014
DOI: 10.1093/jxb/eru300
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression patterns of arabinogalactan proteins in Arabidopsis thaliana reproductive tissues

Abstract: Arabinogalactan proteins (AGPs) are heavily glycosylated proteins existing in all members of the plant kingdom and are differentially distributed through distinctive developmental stages. Here, we showed the individual distributions of specific Arabidopsis AGPs: AGP1, AGP9, AGP12, AGP15, and AGP23, throughout reproductive tissues and indicated their possible roles in several reproductive processes. AGP genes specifically expressed in female tissues were identified using available microarray data. This selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 89 publications
(111 reference statements)
1
63
0
3
Order By: Relevance
“…They serve as recognition signals, nutritional supply or guidance for the pollen tube [13,14]. AGPs have been identified as a group of hydroxyproline-rich glycoproteins, differentially expressed throughout plant development [12][13][14][15]. Previous studies have shown that AGPs were identified in pollen tubes of several plant species, and tube growth was affected by the Yariv phenyl .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They serve as recognition signals, nutritional supply or guidance for the pollen tube [13,14]. AGPs have been identified as a group of hydroxyproline-rich glycoproteins, differentially expressed throughout plant development [12][13][14][15]. Previous studies have shown that AGPs were identified in pollen tubes of several plant species, and tube growth was affected by the Yariv phenyl .…”
Section: Introductionmentioning
confidence: 99%
“…These experimental evidence suggests that AGPs play an important role in pollen tube extension or guidance [17]. Analysis of the Arabidopsis thaliana genome revealed that 47 genes code for AGP polypeptide backbones [15]. ''Classical'' AGPs include an Nterminal secretion sequence, a central domain rich in Pro/Hyp and a C-terminal hydrophobic domain for signaling [12,14,15,17] Herein, we characterized an Arabidopsis AGP1-LIKE PROTEIN (ALP; At3g26110), which have been shown to have 47% homology at the amino acid level to At1g24520.1 (BCP1), POLLEN PROTEIN1 in Brassica campestris [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Podem ainda encontrar-se em corpos multivesiculares intracelulares e corpos multilamelares nos vacúolos (FERGUSON et al, 1999). (COIMBRA et al, 2005;2007;2009;PEREIRA et al, 2014) e Brassica napus (EL-TANTAWY et al, 2013), nesses estudos as AGPs foram diferentementes expressas durante o desenvolvimento gametofítico. Li et al (1992) e Jauh e Lord (1996) verificaram que AGPs se depositam nas paredes dos tubos polínicos e acredita-se que desempenhem importante papel no desenvolvimento da antera e do grão de pólen (PEREIRA et al, 2006;LEVITIN et al, 2008;COIMBRA et al, 2009;MA;SUNDARESAN, 2010;COSTA et al, 2013) .…”
Section: Proteínas Arabinogalactanasunclassified
“…Evidências implicando AGPs na reprodução sexual foram obtidas por diversos grupos, para várias espécies (COIMBRA; SALEMA, 1997;DUARTE, 2003;COIMBRA et al, 2005;EL-TANTAWY et al, 2013) e têm demonstrado ser diferencialmente expressas durante o desenvolvimento gametófito, tornando-se um importante marcador do desenvolvimento reprodutivo (COIMBRA et al, 2007(COIMBRA et al, , 2009PEREIRA et al, 2014). As cinco fases da microsporogênese de A. gamosepala mostram uma clara diferenciação na organização celular e na atividade de RNA.…”
Section: Introductionunclassified